Influencia del entorno familiar en la conducta de los niños/as de 4 años de la I.E N°089 de la ciudad de Rioja - Saavedra Vásquez, Anel Cristin (2015)
The investigation: lnfluence of the familiar environment in the conduct of the children (ace) of 04 years of the Educationallnstitution N o 089 of the city of Rioja in the year 2014 has as aim: to determine the relation between the familiar environment in the conduct of the children (ace) of 04 years; and the specifics were: to describe the familiar environment in his structure, socioeconomic situation, physical environment, familiar dynamics, reaction of the family and familiar conducts in the educational process of the 04-year-old children, to describe the passive, aggressive and assertive conduct of the 04-year-old children and to analyze the relation between the familiar environment with the conduct of the children and 04-year-old girls. Family environment supported by Bravo and Salazar (2006), Muñoz (2009), Rojas (2005), Puche et al (2009) state that is the area in which the child learns behaviors, norms, values, and the benefits; and behavior based on Bleger (1969), Osorio (2013), Goroskieva (sf), they argue that they are manifestations orguided by the mind (mindbody) actions and behaviors that children learn from an early age, whether they are assertive or aggressive. These theoretical assumptions lead to the following hypothesis: The family environment significantly influences the behavior of children (as) 04 years. Methodologically, the design of investigation is descriptive - correlaciona!, with a sample of 22 children of the Educationallnstitution N o 089 of the city of Rioja, and in the process of statistical analysis there was obtained that the hypothesis of investigation is accepted by a value calculated of te = 6,38 and a value to tabulate of ta = ±1,725, checking that the calculated value is major that to tabulate right, which allows that the void hypothesis should be located inside the region of rejection. And the coefficient of Pearson's correlation is of positive correlation with r .. = 0,8188 and this means that the familiar environment influences significantly in the conduct of the children and 4-year-old girls of the Educational institution N ° 089.